Effects of Salviae Miltiorrhizae Radix Hot Aqueous Extract on Nitric Oxide and Prostaglandin E2 Production and on 1,1-diphenyl-2-picryl hydrazyl Radical Scavenging in Macrophages - Yeo In Ho; Lee Cham Kyul; Lee Eun Yong (Korean Pharmacopuncture Institute, 2014)
Objectives: The objective of this study is to investigate the effects of Salviae Miltiorrhizae Radix hot aqueous extract on nitric oxide (NO) and prostaglandin E2 (PGE2) production and on 1,1-diphenyl-2-picryl hydrazyl (DPPH) free-radical scavenging in macrophages. Methods: Salviae Miltiorrhizae Radix (300 g) was heated at 100℃ with distilled water (2 L) for 4 hours. The extract was filtered and concentrated to 100 mL by using a rotary evaporator, was frozen at -80℃, and was then freeze-dried by using a freezing-drying system. The RAW 264.7 macrophage was subcultured by using 10-㎍/mL lipopolysaccharide (LPS). In order to evaluate cytotoxicity, we performed 3-(4,5-dimrthylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays and measured the cell viability. The NO production was measured by using Griess assays, and the PGE2 production was measured by using enzyme immunoassays. The antioxidant activity, the DPPH free-radical scavenging capability, was measured by using the DPPH method. Results: Cell viability with the 1-, 5-, 25-, 125- and 625-㎍/mL Salviae Miltiorrhizae Radix hot aqueous extract was not significantly decreased compared to the cell viability without the extract. When 125 and 625 ㎍/mL of Salviae Miltiorrhizae Radix hot aqueous extract were used, NO production in LPS-stimulated RAW 264.7 macrophages was significantly inhibited compared to that in the control group. When 25, 125, and 625 ㎍/mL of Salviae Miltiorrhizae Radix hot aqueous extract were used, PGE2 production in LPS-stimulated RAW 264.7 macrophages was significantly inhibited compared to that in the control group. The 125- and 625-㎍/mL Salviae Miltiorrhizae Radix hot aqueous extracts had high DPPH free-radical scavenging capabilities in RAW 264.7 macrophages. Conclusion: This study indicates that Salviae Miltiorrhizae Radix hot aqueous extract suppresses NO and PGE2 production and improves DPPH free-radical scavenging capability. Thus, it seems that Salviae Miltiorrhizae Radix hot aqueous extract may have an anti-inflammation effect and antioxidant activity.